2020
DOI: 10.1002/dta.2822
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pharmacology of fentanyl analogs at the human mu opioid receptor and their spectroscopic analysis

Abstract: Opioids are widely misused and account for almost half of overdose deaths in the United States. The cost in terms of lives, health care, and lost productivity is significant and has been declared a national crisis. Fentanyl is a highly potent mu opioid receptor (MOR) agonist and plays a significant role in the current opioid epidemic; fentanyl and its analogs (fentalogs) are increasingly becoming one of the biggest dangers in the opioid crisis. The availability of fentalogs in the illicit market is thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 47 publications
4
32
2
Order By: Relevance
“…To the best of our knowledge fentanyl, morphine, and buprenorphine have never been compared using an assay based on the aequorin system, but a few studies using human receptors have been conducted using other reporting systems. Lipinski et al 5 and Hassanien et al 23 reported binding affinities of fentanyl of 1.2 and 1.6 nM, respectively. Using a GTPγS binding assay, Olson et al 9 used the same cell line as in this study and determined the EC 50 values for morphine and buprenorphine to be 130 and < 0.1 nM, respectively with efficacies of 96% and 35% (compared with endomorphine‐2).…”
Section: | Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge fentanyl, morphine, and buprenorphine have never been compared using an assay based on the aequorin system, but a few studies using human receptors have been conducted using other reporting systems. Lipinski et al 5 and Hassanien et al 23 reported binding affinities of fentanyl of 1.2 and 1.6 nM, respectively. Using a GTPγS binding assay, Olson et al 9 used the same cell line as in this study and determined the EC 50 values for morphine and buprenorphine to be 130 and < 0.1 nM, respectively with efficacies of 96% and 35% (compared with endomorphine‐2).…”
Section: | Discussionmentioning
confidence: 99%
“…Using a GTPγS binding assay, Olson et al 9 used the same cell line as in this study and determined the EC 50 values for morphine and buprenorphine to be 130 and < 0.1 nM, respectively with efficacies of 96% and 35% (compared with endomorphine‐2). Also using a GTPγS binding assay, Hassanien et al 23 reported an EC 50 value of 32 nM for fentanyl, while the Drug Enforcement Administration reported EC 50 values of 32 nM and 17 nM for fentanyl and morphine, respectively. Using assays based on cAMP, Kuo et al 11 reported IC 50 values of 180, 0.2, and 1 nM for morphine, buprenorphine, and fentanyl, respectively, while Yu et al 10 reported EC 50 values of 5.3 and 0.02 nM for morphine and buprenorphine, respectively.…”
Section: | Discussionmentioning
confidence: 99%
See 3 more Smart Citations